f(x) = 2x+3/x-4 Work out f ^–1 (x)

first off, replace all x values with y and all y values with x, which gives us, X = 2Y + 3 / Y - 4 rearrange to give, X(Y - 4) = 2Y + 3 expand the bracket, XY - 4X = 2Y + 3 rearrange to get all Y terms on one side, XY -2Y = 4X + 3 factorise to give Y(X - 2) = 4X + 3 and finally rearrange to get, Y = 4X + 3/X - 2

Answered by Dean J. Maths tutor

2478 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

Sketch the graph of y = 5 - 7x


Simplify (x + 3)(2x + 5) - (x - 1)


Solve the simultaneous equations: 8x + 2y =46, and 7x + 3y = 47


Expand and simplify 6x^2(x-1)(x+2)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences